2019
DOI: 10.1177/1059840519846089
|View full text |Cite
|
Sign up to set email alerts
|

School Health Policy Implementation: Facilitators and Challenges

Abstract: Schools are uniquely positioned to impact student health and academic outcomes through health and wellness policies. The purpose of this study was to describe factors influencing implementation of school health and wellness policies, specifically those focused on physical activity and nutrition. In-depth, stakeholder interviews were conducted with key informants at eight Chicago Public Schools (K–eighth grade). Data were analyzed using summative content analysis. Two themes were identified, facilitators and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…School nurses are looked to as key figures and role models for student (Walker, 2014) and staff (Wood et al, 2019) health and wellness and are in ideal positions to assist school leaders with facilitating evaluations of school wellness environments and policies. While factors associated with school nurses, such as their limited time and availability, have been identified as challenges to implementing school wellness policies and practices (Cygan et al, 2019), the results of this study provides schools with a concise set of 35 items that can be adopted and feasibly implemented to facilitate evaluation of the overall school wellness environments and policies with reasonable accuracy. Considering school nurses work within and across multiple sectors of the school environment, they can be key advocates for completing school-wide assessments of wellness environments and policies and doing so accurately.…”
Section: Implications For School Nursingmentioning
confidence: 99%
“…School nurses are looked to as key figures and role models for student (Walker, 2014) and staff (Wood et al, 2019) health and wellness and are in ideal positions to assist school leaders with facilitating evaluations of school wellness environments and policies. While factors associated with school nurses, such as their limited time and availability, have been identified as challenges to implementing school wellness policies and practices (Cygan et al, 2019), the results of this study provides schools with a concise set of 35 items that can be adopted and feasibly implemented to facilitate evaluation of the overall school wellness environments and policies with reasonable accuracy. Considering school nurses work within and across multiple sectors of the school environment, they can be key advocates for completing school-wide assessments of wellness environments and policies and doing so accurately.…”
Section: Implications For School Nursingmentioning
confidence: 99%
“…The study evaluated the efficacy, feasibility, and safety of home-based activity rehabilitation programs for children with diplegic CP. The results of the study and methodology used suggested that dance exercise was a good choice to be added to this activity package for diplegic CP sufferers ( Cygan et al, 2020 ; Goswami et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Darlington et al (2018), implementing multifaceted public health programs is challenging in the school setup. Cygan et al (2020) also affirmed that among the challenges faced by schools are limited availability of school nurses and budget.…”
Section: Challenges Encountered In the Utilization Of School Health Servicesmentioning
confidence: 99%